2017
DOI: 10.1371/journal.pone.0168197
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Fish Sentience, Welfare and Humane Slaughter by Highly Educated Citizens of Bogotá, Colombia and Curitiba, Brazil

Abstract: Discussions on farm animal welfare have become frequent, especially in developed countries. The aim of this research was to study the perception of fish sentience, welfare and slaughter by highly educated citizens from Bogotá, Colombia, and Curitiba, Brazil. An online survey with 12 questions presented as open-ended, multiple choice and 5-point Likert-type scale formats was available to respondents. Answers from 395 participants in Bogotá and 387 in Curitiba were analyzed, and results are presented in the orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 55 publications
4
9
0
Order By: Relevance
“…Opinions about animal emotions that were revealed by this study show that mammals are perceived as having a higher degree of sentience when compared to other animals. This finding is in agreement with other studies, 2629,30 which reported that species more phylogenetically distant from humans were considered to be less sentient. This has also been described in another study, 31 which highlighted what seems to be a common opinion in science — that dogs are closer to humans, as compared to mice and rats — and for this reason experiments on the latter two species are considered more acceptable.…”
Section: Resultssupporting
confidence: 94%
“…Opinions about animal emotions that were revealed by this study show that mammals are perceived as having a higher degree of sentience when compared to other animals. This finding is in agreement with other studies, 2629,30 which reported that species more phylogenetically distant from humans were considered to be less sentient. This has also been described in another study, 31 which highlighted what seems to be a common opinion in science — that dogs are closer to humans, as compared to mice and rats — and for this reason experiments on the latter two species are considered more acceptable.…”
Section: Resultssupporting
confidence: 94%
“…According to Pedrazzani et al (20), 87% of people interviewed in the town of Araucária, Southern Brazil, believed that fish are capable to feel pain and 85% that common slaughter methods cause suffering. Similar results were obtained by Rucinque et al (88), who conducted an interview with highly educated citizens from Bogotá and Curitiba. From the participants, 79.7 and 71.8% perceived fish as sentient animals, and 76.0 and 72.0% believed that fish should be included in humane slaughter regulations, respectively.…”
Section: Discussionsupporting
confidence: 87%
“…Human perceptions and emotions influence actions and decisions and as such, improving human attitudes towards a species can lead to improvements in their care and strengthen support for their protection [ 47 , 107 ]. Given the relatively uncharitable public opinion towards fish in general and lack of awareness around fish cognition, sentience and emotion [ 108 , 109 , 110 ], research establishing the potential for positive human–fish interactions is particularly needed to counteract baseline expectations and improve perceptions of fishes’ worth and moral status. Additional work exploring human–fish interactions thus has the potential to have significant downstream consequences for the welfare of fishes including increasing public support for fish protection and regulations.…”
Section: Discussionmentioning
confidence: 99%